Improving the Yield of Xenocoumacin 1 by PBAD Promoter Replacement in Xenorhabdus nematophila CB6 - Youcai Qin; Fenglian Jia; Xiaohui Li; Beibei Li; Jie Ren; Xiufen Yang; Guangyue Li (Agriculture, 2021)
Xenocoumacin 1 (Xcn1), which is produced by Xenorhabdus nematophila CB6, exhibits strong inhibition activity against plant pathogens, especially fungi and oomycetes. Therefore, it has attracted interest in developing it into a novel biofungicide applicable for plant protection. However, its low yield with concomitant high cost during the fermentation process limits its widespread application. In this study, we replaced the native promoter of xcnA with the arabinose-inducible araBAD promoter (PBAD), a well-known and widely used promoter for expressing heterologous genes, to evaluate its effects on Xcn1 yield and antimicrobial activity. Compared with wildtype strain, the fermentation yield of Xcn1 was improved from 68.5 mg/L to 249.7 mg/L (3.6-fold) and 234.9 mg/L (3.4-fold) at 0.5% and 1.0% L-arabinose concentration, respectively. We further explored the transcription level of the biosynthesis related genes of Xcn1 and found that their upregulation resulted in the yield improvement of Xcn1. Moreover, the antimicrobial activity of Xcn1 against Bacillus subtilis and Phytophthora capsici was determined by agar diffusion plate and growth inhibition assay, as expected, it was also found to be enhanced. The promoter-replacement strategy utilized here improves the yield of Xcn1 efficiently, which provides a basis for the industrial production of Xcn1.